Find the value of the square root of \[\sqrt{20+\sqrt{3}+\sqrt{28-10\sqrt{3}}}\] is:
(a) zero
(b) 25
(c) 49
(d) None of the above
Answer
Verified
468k+ views
Hint: To solve this question, we will start from the right of the given expression and then try to eliminate the square root by taking a square inside the square root. To do so, we will use 28 = 25 + 3 and \[10\sqrt{3}\] as \[2\times 5\times \sqrt{3}\] and then finally use the formula \[{{\left( a-b \right)}^{2}}={{a}^{2}}+{{b}^{2}}-2ab\] to get the result.
Complete step-by-step solution
Let us assume a variable as \[y=\sqrt{20+\sqrt{3}+\sqrt{28-10\sqrt{3}}}.\] Let us write 28 as 25 + 3 and then write \[10\sqrt{3}\] as \[2\times 5\times \sqrt{3}.\] So, putting all these substitutions in y, we get,
\[y=\sqrt{20+\sqrt{3}+\sqrt{25+3-2\times 5\times \sqrt{3}}}......\left( i \right)\]
Consider the identity given as \[{{\left( a-b \right)}^{2}}={{a}^{2}}+{{b}^{2}}-2ab.\] Let a = 5 and \[b=\sqrt{3}.\] Using this above stated identity using a = 5 and \[b=\sqrt{3}.\] We get,
\[{{\left( 5-\sqrt{3} \right)}^{2}}={{\left( 5 \right)}^{2}}+{{\left( \sqrt{3} \right)}^{2}}-2\times 5\times \sqrt{3}\]
\[\Rightarrow {{\left( 5-\sqrt{3} \right)}^{2}}=25+3-2\times 5\times \sqrt{3}......\left( ii \right)\]
Comparing equation (i) and (ii), we see that \[25+3-2\times 5\times \sqrt{3}\] can be replaced by \[{{\left( 5-\sqrt{3} \right)}^{2}}.\]
Replacing \[25+3-2\times 5\times \sqrt{3}\] by \[{{\left( 5-\sqrt{3} \right)}^{2}}\] in equation (i), we get,
\[y=\sqrt{20+\sqrt{3}+\sqrt{{{\left( 5-\sqrt{3} \right)}^{2}}}}\]
Cancelling the square root and square, we have,
\[\Rightarrow y=\sqrt{20+\sqrt{3}+\left( 5-\sqrt{3} \right)}\]
\[\Rightarrow y=\sqrt{20+5+\sqrt{3}-\sqrt{3}}\]
\[\Rightarrow y=\sqrt{25}\]
\[\Rightarrow y=5\]
Hence, the value of the term \[\sqrt{20+\sqrt{3}+\sqrt{28-10\sqrt{3}}}\] is 5.
Hence, the right option is (d).
Note: Do not proceed with these types of questions by assuming some variable to \[\sqrt{3},\] let \[x=\sqrt{3},\] then y would become \[y=\sqrt{20+x+\sqrt{28-10x}}.\] Then for further processing, take the square on both the sides, \[{{y}^{2}}=20+x+\sqrt{28-10x}.\] Then the equation will be of two variables and would have the complex square and square root. Then the equation would become difficult to solve. So, it is better to start by eliminating the square root by forming the perfect square inside.
Complete step-by-step solution
Let us assume a variable as \[y=\sqrt{20+\sqrt{3}+\sqrt{28-10\sqrt{3}}}.\] Let us write 28 as 25 + 3 and then write \[10\sqrt{3}\] as \[2\times 5\times \sqrt{3}.\] So, putting all these substitutions in y, we get,
\[y=\sqrt{20+\sqrt{3}+\sqrt{25+3-2\times 5\times \sqrt{3}}}......\left( i \right)\]
Consider the identity given as \[{{\left( a-b \right)}^{2}}={{a}^{2}}+{{b}^{2}}-2ab.\] Let a = 5 and \[b=\sqrt{3}.\] Using this above stated identity using a = 5 and \[b=\sqrt{3}.\] We get,
\[{{\left( 5-\sqrt{3} \right)}^{2}}={{\left( 5 \right)}^{2}}+{{\left( \sqrt{3} \right)}^{2}}-2\times 5\times \sqrt{3}\]
\[\Rightarrow {{\left( 5-\sqrt{3} \right)}^{2}}=25+3-2\times 5\times \sqrt{3}......\left( ii \right)\]
Comparing equation (i) and (ii), we see that \[25+3-2\times 5\times \sqrt{3}\] can be replaced by \[{{\left( 5-\sqrt{3} \right)}^{2}}.\]
Replacing \[25+3-2\times 5\times \sqrt{3}\] by \[{{\left( 5-\sqrt{3} \right)}^{2}}\] in equation (i), we get,
\[y=\sqrt{20+\sqrt{3}+\sqrt{{{\left( 5-\sqrt{3} \right)}^{2}}}}\]
Cancelling the square root and square, we have,
\[\Rightarrow y=\sqrt{20+\sqrt{3}+\left( 5-\sqrt{3} \right)}\]
\[\Rightarrow y=\sqrt{20+5+\sqrt{3}-\sqrt{3}}\]
\[\Rightarrow y=\sqrt{25}\]
\[\Rightarrow y=5\]
Hence, the value of the term \[\sqrt{20+\sqrt{3}+\sqrt{28-10\sqrt{3}}}\] is 5.
Hence, the right option is (d).
Note: Do not proceed with these types of questions by assuming some variable to \[\sqrt{3},\] let \[x=\sqrt{3},\] then y would become \[y=\sqrt{20+x+\sqrt{28-10x}}.\] Then for further processing, take the square on both the sides, \[{{y}^{2}}=20+x+\sqrt{28-10x}.\] Then the equation will be of two variables and would have the complex square and square root. Then the equation would become difficult to solve. So, it is better to start by eliminating the square root by forming the perfect square inside.
Recently Updated Pages
Identify how many lines of symmetry drawn are there class 8 maths CBSE
State true or false If two lines intersect and if one class 8 maths CBSE
Tina had 20m 5cm long cloth She cuts 4m 50cm lengt-class-8-maths-CBSE
Which sentence is punctuated correctly A Always ask class 8 english CBSE
Will Mr Black be at home Saturday evening Yes hell class 8 english CBSE
An electrician sells a room heater for Rs 3220 gaining class 8 maths CBSE
Trending doubts
How is the Lok Sabha more powerful than the Rajya class 8 social science CBSE
Write a letter to your friend telling himher how you class 8 english CBSE
Write the following in HinduArabic numerals XXIX class 8 maths CBSE
Differentiate between natural disasters and manmade class 8 social science CBSE
Differentiate between the farms in India and the U class 8 social science CBSE
The strategy of Divide and rule was adopted by A Lord class 8 social science CBSE